Analysis of the Influence of Mudharabah Financing, Musyarakah Financing, Capital Adequacy Ratio, and Non-Performing Financing on Banking Performance with Qardhul Hasan as Control Variable (Case Study on Islamic Commercial Banks in Indonesia in 2013-2017) - Alfiyah, Mike Ayu; Widiastuti, Ekaningtyas; Sudarto, Sudarto (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
This research entitled